Small Modular Reactors: Licensing constraints and the way forward. (15th March 2015) - Sainati, Tristano; Locatelli, Giorgio; Brookes, Naomi
Abstract: SMR (Small Modular Reactor) is an acronym for a group of nuclear power plant designs receiving an increasing deal of attention from the industry and policy makers. A large number of SMRs need to be built in the same site and across the word to compensate diseconomies of scale and be cost competitive with large reactors and other base-load technologies. A major barrier is the licensing process, historically developed for large reactors, preventing the simply deployment of several identical units in different countries. This paper, discussing Ramana, Hopkins and Glaser [1], enlarges the view to all the SMR-related implications on the licensing process, presenting their legislative implications and market effects.